Hadith Peniupan Roh Semasa Tempoh Pranatal: Analisis Menurut Perspektif Muḥaddithīn: Hadith On Soul Being Breathed in Foetus In Pranatal Period: Analysis By Muḥaddithīn Perspective - Nasir, Khairulnazrin; Ahmad, Khadher` (Online Journal of Research in Islamic Studies, 2020)
The soul is an unseen entity created by Allah and is the essence of human life and some other beings. The souls are blown into the foetus by the angels during the prenatal stage in the womb. It is explained in the Hadith narrated by Ibn Mas’ūd RA’s which is also the ground for the issue regarding the entrance of the soul into the human body. The question is, what is the discussion and perspective of the muḥaddithīn scholars about the Hadith. Therefore, the purpose of this paper is to explain the source of the Hadith and to focus on the muḥaddithīn discussions on both the riwāyah and the rhäyah. The framework of this study is qualitative, which draws from library data, especially turath (classical) books in the science of Hadith, as well as descriptive analysis. The focus of the study is on the issue of the breathing in of the soul into the foetus, despite other themes in the Hadith. Past studies/This study found that this Hadith was narrated in eight primary sources of Hadith. The authors of the books of Hadith placed the Hadith in this study under three main themes; whether it’s about the creation of man, the writing of destiny, or the role of the angels who blow the souls into the foetus. The Hadith of the study is also discussed from various other perspectives, which still related to the soul. In conclusion, this paper presented a fact about the unseen world that cannot be grasped by modern medical science.